Rationalizing Critical Cost Overrun Factors on Public Sector Housing Programmes - Aaron Anil Chadee; Hector Hugh Martin; Abrahams Mwasha; Festus Otuloge (Ital Publication, 2022)
The cost overrun phenomenon on projects worldwide creates a major source of risk that warrants investigation. The prevailing factor school of thought provides strong empirical evidence that critical factors contributing to cost overruns are both context-specific and project-specific. Although many studies have been conducted identifying factors and causes of cost overruns, very few studies have investigated root causes. Additionally, a limited body of knowledge is available within the context of Small Island Development States (SIDS). To fill this gap, the objectives of this study were to identify and determine the main critical factors contributing to the cost overrun phenomenon in public sector social housing programmes (PSSHPs). These selected factors were thereafter categorized under leading root causes, and their severity was determined based on primary stakeholders’ perspectives. One hundred and twenty-three factors were identified from the literature, of which forty-one critical factors were extracted and grouped under four root causes based on a pilot survey of relevant public sector housing experts in the Trinidadian and Jamaican construction sectors. These refined factors and root causes were formulated into a questionnaire survey. One hundred and five responses were obtained from professionals who had a minimum of five years’ experience in various phases of public housing delivery. The severity of these critical factors was evaluated, ranked, and categorized using the relative importance index (RII) approach. The findings uncovered the leading root cause, which is political in nature. The top five critical factors are the selection of politically aligned contractors, the intentional design of inadequate contracts, the project actors' deliberately underestimating costs, the partisan project management team, and strategic misrepresentation. These findings are unique to SIDS and contribute to knowledge to reframe contemporary project management practices, which focus mainly on technical causes. Finally, as existing technical solutions are ineffective in curbing cost overruns in PSSHPs, these findings also inform public sector policymakers to focus on prioritization, control, and mitigation of political risks in formulating effective governance mechanisms. Doi: 10.28991/ESJ-2022-06-03-016 Full Text: PDF